2019
DOI: 10.3390/rs11242985
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Characteristics at Two Locations in the Tropical Andes by Means of Vertically Pointing Micro-Rain Radar Observations

Abstract: In remote areas with steep topography, such as the Tropical Andes, reliable precipitation data with a high temporal resolution are scarce. Therefore, studies focusing on the diurnal properties of precipitation are hampered. In this paper, we investigated two years of data from Micro-Rain Radars (MRR) in Cuenca, Ecuador, and Huaraz, Peru, from February 2017 to January 2019. This data allowed for a detailed study on the temporal precipitation characteristics, such as event occurrences and durations at these two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 47 publications
5
13
0
Order By: Relevance
“…These results about short rainfall duration support evidence from previous observations [4,14]. Orellana-Alvear et al [4] analyzed the rainfall events duration using the LPM disdrometer and found that the mean event duration is around 3 h. In the same way, Seidel et al [14] confirmed that the short duration events are dominant in this study area by using MRR data. Furthermore, the short duration of the events evidenced the necessity of high temporal resolution to capture their variability.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…These results about short rainfall duration support evidence from previous observations [4,14]. Orellana-Alvear et al [4] analyzed the rainfall events duration using the LPM disdrometer and found that the mean event duration is around 3 h. In the same way, Seidel et al [14] confirmed that the short duration events are dominant in this study area by using MRR data. Furthermore, the short duration of the events evidenced the necessity of high temporal resolution to capture their variability.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the short duration of the events evidenced the necessity of high temporal resolution to capture their variability. However, the instruments' time resolution (e.g., rain gauge) limit capturing the variability in these events [14,68]. Padrón et al [68] already discussed the influence of different instrument time resolution (rain gauge and disdrometer laser) in rainfall data after finding that the rain gauge underestimates rainfall catch.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In areas characterized by a coarse network of operational rain gauge stations, highly variable spatiotemporal precipitation patterns cannot fully be captured. This particularly holds for regions with a complex climate and topography (Seidel et al, 2019). Ecuador is one of such areas; the Andes Mountains characterize the country with the highest peaks exceeding elevations of 6268 m above sea level (m.a.s.l.…”
Section: Introductionmentioning
confidence: 99%